Isolation of the neutralization ScFvs against HBV infection from the immunized population - Bai, Yin; Chen, Yanmin; Zhang, Nan; Guo, Xiaochen; Zhao, Jingzhuang; Wang, Fuxiang; Xu, Pengfei; Yuan, Qingyan; Qi, Jianying; Wang, Wenfei; Li, Deshan; Ren, Guiping (Current Pharmaceutical Biotechnology, 2015)
For a long time, researchers have attempted to replace human plasmaderived immunoglobulin against HBV with recombinant HBV antibodies for therapeutic purposes, but failed to develop the products. One of the reasons may be lack of high throughput antibody screening tool. In this study, we screened an antibody library from immunized subjects by a powerful bacterial display technology. The capacity of the ScFv library was 10sup>9/sup>, 117 individual clones against HBV pre- S1 were initially selected and sequenced, the homology of these clones ranged from 59.7% -68.7%. Ten clones were randomly selected based on florescence intensity by FACS. The ScFv antibodies were expressed in E.coli/ and purified to examine their neutralization ability. First, we tested the ability of these clones to block the binding of the pre-S1 polypeptide to the HBV sensitive cells Chang liver cells and HepG2 cells, then, we examined the ability of these clones to inhibit the infection of the Change liver cells by HBV released from HepG2.2.15 cells by detection of viral DNA and hepatitis B virus e antigen (HBeAg) in the supernatant of Chang liver cells. Results showed that 4 (clone 3, 7, 9 and 31) out of the ten clones could significantly reduce the binding of pre-S1 polypeptide to Chang liver cells in a dose-dependent manner. Treatment with the same clones (clone 3, 7, 9 and 31) could dramatically reduce the contents of HBV DNA in the media of the infected Chang liver cells by 29.4, 7.89, 58.8, 76.9, respectively, and the amount of HBeAg by 60.2%, 32.6%, 66.1% and 68.1%, respectively. These results suggest that these clones can neutralize HBV infection and have the potential to become therapeutic antibodies against HBV infection to replace the human plasma-derived immunoglobulin
Keywords: HBV